Investigating the potential of using hydrocyclone-fine screen hybrid systems to improve the performance of classification circuits - Muketekelwa, Saliya L (Centre for Minerals Research, 2018)
Classification is an integral part of comminution operations that controls the performance of the circuit. Hydrocyclones are normally used to perform the classification function. They offer numerous advantages that include, the ability to handle high throughputs, low floor space occupation and relatively low capital and running costs. Despite these advantages, hydrocyclones are inherently inefficient classifiers as they are predominantly dependent on hydrodynamics to effect separation. This effect is more prominent in operations handling complex ores such as a dual-density ore, where the heavy fine particles are misplaced to the underflow and the lighter middling particles report to the overflow. Several attempts have been made to improve the separation efficiency of cyclones either by modification of the cyclone or use of multi-stage cycloning. Most of the results obtained from experimental and simulation studies have shown considerable improvements. Even though some have not yet found wide application in the minerals industry due to practical limitations related to control and unstable operations. More recently, fine screening has gained recognition in the classification role. This development has allowed the use of fine screens in closed-circuit grinding operations resulting in significant metallurgical and economic benefits. Screens provide a sharper cut at the desired size and reduce the fraction of fines bypassing classification compared to hydrocyclones but have capacity limitations at smaller apertures. In an effort to mitigate the classification challenges of both the hydrocyclone and fine screen, this study investigated the potential of combining the high throughput performance of the hydrocyclone operation and the high precision classification characteristics of fine screening to result in a hybrid classification circuit Plant scale tests were conducted using five different classification circuit configurations at an operational Base Metal Concentrator treating a polymetallic ore. The classification circuit configurations considered included (i) a two-stage hydrocyclone with primary underflow reclassification (ii) an inclined hydrocyclone, (iii) a fine screen and (iv) selected permutations of hybrid circuit designs that included a hydrocyclone-fine screen (2 stage) and two hydrocyclones-fine screen (3 stage) variants of the hybridised configurations. The efficiency curves and their respective key performance indicators were used to assess the performance of the circuit configurations tested. The results showed that classification circuits that included fine screens exhibited higher sharpness of separation compared to circuit configurations comprised of hydrocyclones. The fine screen configuration showed the sharpest separation while the hydrocyclone-fine screen hybrid configurations gave relatively higher separation efficiencies than the configurations with hydrocyclones only. The overall sharpness of separation values obtained for the two stage and three-stage hybrid circuits were 3.0 and 2.4, respectively. The two-stage hydrocyclone and inclined hydrocyclone circuits had sharpness of separation values of 1.7 and 0.5, respectively. The inclined hydrocyclone circuit configuration performed the poorest. Furthermore, the two-stage hybrid circuit showed a higher degree of separation compared to the three-stage hybrid configuration. However, it was observed that a finer corrected cut size was realised for the three-stage hybrid circuit design. The fishhook effect was seen at particle sizes less than 38μm for the configurations incorporating a fine screen and an inclined hydrocyclone. Notably, the effect appeared to be more pronounced in configurations involving a fine screen stage. The results have shown that application of hybrid classification configurations can improve the performance of classification circuits. In addition, reclassification of hydrocyclone underflow on fine screens will results in a sharper classification while reclassifying the overflow stream on fine screens will provide a clean circuit final product. An evaluation of the capital and operating costs associated with fine screens should be done to determine the economic feasibility of incorporating the units in conventional milling circuits.